Re-reading Gender-Related Verses through Qira’at Variation: Semantic and Legal-Interpretive Implications in Surat al-Nisa’ - Hasanah, Ulfatun (Tashwirul Afkar, 2025)
This article examines how qira’at variation in selected gender-related verses of Surat al-Nisa’ shapes semantic expansion and legal-interpreive consequences in Qur’anic exegesis. The study is motivated by the persistence of monolithic readings of gender verses in contemporary Muslim discourse, particularly on issues such as polygamy, violence against women, household authority, and bodily contact in ritual contexts. Using a qualitative library research design, this article employs a Qur’anic exegesis approach with particular attention to thematic tafsir and qira’at analysis. The unit of analysis consists of variant readings in Q. al-Nisa’ 4:3, 4:19, 4:34, and 4:43. Primary data are drawn from the relevant Qur’anic verses, classical qira’at works, and tafsir literature, while secondary data are taken from scholarly studies on gender-related Qur’anic interpretation. The data are analyzed through comparative-textual and interpretive analysis. The study finds, first, that qira’at variation produces semantic expansion by opening broader lexical, relational, and ethical possibilities in gender-related verses. Second, these semantic differences generate distinct legal-interpreive consequences, including stricter readings of polygamy, broader protections against violence toward women, more reciprocal understandings of household responsibility, and plural ritual-legal rulings concerning bodily contact. Third, these findings support a re-reading of gender verses beyond a monolithic Hafs-based interpretive framework. This article argues that qira’at plurality should be treated not as a peripheral technical issue, but as an internal methodological resource for more dialogical, contextual, and textually grounded gender-sensitive Qur’anic interpretation.